Negotiating the Boundaries of Professional Subtitling. The Case of Finnish Subtitlers and Their Online Community - Tuominen, Tiina (HERMES - Journal of Language and Communication in Business, 2018)
In recent years, the Finnish subtitling field has undergone significant changes, which have caused instability in subtitlers’ working conditions. Subtitlers have responded to these changes by working together towards a more unified professional community. One important means in these efforts has been an active online presence consisting of, among other things, a website and a blog. The subtitlers’ online presence could be characterised as an element of a “professional project” (Tyulenev 2014: 68–69), an attempt to institutionalise the profession and to search for social recognition. One aspect of a professional project is to draw the boundaries of the profession and to determine criteria for acceptance into the professional community. The definition of professional boundaries is a recurrent theme on the Finnish subtitlers’ website and blog. The subtitlers’ case therefore provides an enlightening example of how a heterogeneous professional field can attempt to improve its standing by determining its own boundaries. This article will explore how Finnish subtitlers define the boundaries of their profession on their website and blog, what criteria they present for inclusion in their professional community, and how exclusion from the community is expressed. The analysis will demonstrate that a number of professional practices, such as adherence to local subtitling traditions, are used as a way of determining the behaviour of a professional subtitler. As a consequence, the definition of professional boundaries emerges as a central argument in the subtitlers’ professional project, becoming a strategy for unifying the subtitlers’ community and advocating for a more stable status.